Words of Advice: How to be a good Principal Investigator - Banks, Lawrence (The FEBS journal, 2021)
In this instalment of The FEBS Journal’s Words of Advice series, Lawrence Banks, Director‐General of the International Centre for Genetic Engineering and Biotechnology (ICGEB) and Group Leader of the Tumour Virology Laboratory at the same institute, provides advice on cultivating a supportive and productive research group environment. His tips and recommendations are tailored for each stage of the career path typically followed by a principle investigator.